Pharmacological support in the perioperative period of implantation of a polypropylene mesh prosthesis (experimental study) - E. E. Lukoyanychev; S. G. Izmajlov; A. E. Leontev; A. A. Mironov; V. O. Nikolskij; D. A. Evsjukov; V. A. Emelyanov (Исследования и практика в медицине)
Purpose of the study. was to improve the technology of prosthetic repair of the anterior abdominal wall patients with hernias by means of pharmacological regulation of the local and systemic inflammatory response and stimulation of reparative regeneration.Materials and methods. The study was carried out on 52 pure line rats in vivarium. All animals have on-lay implantation of a polypropylene mesh imlantant. Group I have no specific pharmacological treatment receive (0.9 % sodium chloride solution); group II – receive solution of xymedon, group III – potassium orotate, group IV – methyluracil.Results. Identified that all investigated drugs of the pyrimidine series (xymedon, potassium orotate, methyluracil) have a significant effect on the local and systemic inflammatory process. The growth of IL 10 and TNF-a are associated with an increase in the area of liquid inclusions. The use of potassium orotate and methyluracil in the postoperative period is inappropriate, as it is associated with an increased risk of hemorrhage and acute paraprosthetic fluid accumulations. Taking xymedon after surgery is associated with an accelerated growth of blood vessels and granulation tissue, a decrease in fluid inclusions, but is associated with an insignificant increase in the risk of tissue hemorrhage.Conclusion. Pharmacological regulation of inflammatory and regenerative processes with xymedon in the perioperative period of prosthetic repair could guide the development of surgical treatment of patients with abdominal hernias, which requires further clinical study.